SEORANG PENDERITA HAMIL DENGAN LEUKEMIA MIELOID AKUT - Sukrawan, Gede; Losen Adnyana, Wayan; Suega, Ketut (journal of internal medicine; Vol. 12, No. 2 Mei 2011, 2012)
Leukemia during pregnancy is extremely rare, the estimate one per100,000 pregnancies each year. Intrauterine growth disorders have been reported in pregnant women with untreated AML. A pregnant female patient, 28 years old, Balinese, private employ came with chief complain fever, sweaty, nausea and vomiting, body weekly, Physical examination: anemic, pale, blood pressure; 120/80mmHg, pulse 88 x/minute, respiration 20 x/minute, axillary temperature of 36.7 degrees Celsius, heart andlung arenormal, Abdoment: fundus uteri-high processusxipoideus, distention and bowel sounds normal. Laboratory January 14th 2011: leukocyte 63,2 103/ul, Hb 11.7 g/dl, hematocrite 33.6%, MCV 30.7 pg, trombocite 40 103/ul, anatomicalpathology on November 26th 2009 with increasing blast dysplasia eritroid series, allowing a leukemia acute. January 16th 2010 chemotherapyAra-C 150 mg in 500 ml NaCl 0.9% 24 hours for 7 days and daunorubicine 60 mg IV bolus for 3 days. January 18th 2010 laboratory resultleukosit 46.2 x 103/ul, Hb 9.2 g/dl, hematocrite 26.3%, MCV 87.4 fl, MCH 30.4 pg and thrombocyte 10 x 103/ul. The patient had complite remission after chemoterapy and laboratory results on February 12th 2010 were leucocyte 7.02 x 103/ul, Hb 8.6 g/dl, hematocrite 25.5%, MCV 74.5 fl, MCH 25.5 and thrombocyte 125 x 103/ul. The baby was born with normal condition with operation. Acute leukemia in pregnancy should be managed together hematologist, obstetrics-gynaecology and neonatologists.
Keywords: AML, pregnancy, complete remission